An investigation of the effects of high molecular weight glutenin subunits on wheat tortilla quality - Pierucci, Valquiria Resende Malaspina (Kansas State University, 2008)
The wheat tortilla is a chemically leavened circular light colored flat bread. Desirable characteristics for good quality tortilla include large diameter, softness, flexibility and long shelf stability. Important components influencing quality are wheat flour properties, which have not been optimized for tortilla industrial production thus far. The studies presented here investigated the effects of high molecular weight glutenin subunits (HMW-GS) on tortilla quality. Two approaches were employed: biotypes derived from Centurk and OK102 cultivars expressing defined HMW-GS compositions and transgenic wheat lines over-expressing HMW-GS 10. Analysis of protein expression and protein extractability were conducted to characterize wheat flours and suitable assays carried out to determine the respective dough properties. Tortillas were prepared by the hot-press method and quality parameters were measured at days 0, 2, 4, 7 and 14. Tortillas derived from Centurk biotypes possessing HMW-GS 2*, 7+9, 2+12, 2*, 7+8, 5+10 and 2*, 7+9, 5+10 exhibited superior texture profiles over time, but smaller diameters than the biotype 2*, 7+8, 2+12. Tortillas containing HMW-GS 7+9 and 2+12 revealed a texture profile similar to tortillas containing 5+10. Tortillas from the OK biotype 2*, 7+9, 3+12 exhibited larger diameter and texture profiles equivalent to tortillas containing 5+10. Therefore, this biotype showed the best quality within this cultivar. Tortillas derived from transgenic flours over-expressing HMW-GS 10 exhibited an undesirable rough appearance with decreased diameter, greater thickness, lower rollability scores, lower stretchability and greater rupture force over time. Over-expression of HMW-GS 10 in a wheat line containing 1RS-translocation did not promote the same deleterious effects in tortilla quality as it did in transgenic lines without 1RS translocation.
Keywords: High molecular weight glutenin subunits; HMW-GS; Wheat tortilla quality; Agriculture, Food Science and Technology (0359)